Respostas
respondido por:
2
a
( 2/4)⁻² = ( 4/2)² = 16/4 = 4 ***
expoente negativo > inverte base e passa expoente para +
b
( 1/2)⁻³ = 2³ = 8 ***
c
( 4/5)⁻² = ( 5/4)² = 25/16 ***
d
( 8 )⁻² = ( 2³)⁻² = ( 2)⁻⁶ = ( 1/2)⁶ = 1/64 ***
multiplica expoentes 3 * -2 = -6
e
( 0,6)⁻² = ( 6/10)⁻² = ( 10/6)² = 100/36 ***
se ajudei não esqueça de me avaliar
( 2/4)⁻² = ( 4/2)² = 16/4 = 4 ***
expoente negativo > inverte base e passa expoente para +
b
( 1/2)⁻³ = 2³ = 8 ***
c
( 4/5)⁻² = ( 5/4)² = 25/16 ***
d
( 8 )⁻² = ( 2³)⁻² = ( 2)⁻⁶ = ( 1/2)⁶ = 1/64 ***
multiplica expoentes 3 * -2 = -6
e
( 0,6)⁻² = ( 6/10)⁻² = ( 10/6)² = 100/36 ***
se ajudei não esqueça de me avaliar
Perguntas similares
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás